Aboveground Biomass and Nutrient Pools in Two Evergreen Oak Stands of the Middle Moroccan Atlas Area - Boulmane, Mohamed; Santa-Regina, Ignacio; Khia, Abderrahim; Abbassi, Hassan; Halim, Mohamed (Arid Land Research and Management, 2013)
The aboveground tree biomass and nutrient pools, litterfall, and weight loss of litter due to decomposition have been measured in two permanent plots of evergreen oak forest (Quercus ilex L.) of the Middle Moroccan Atlas area (Tafachna and Reggada). The aboveground biomass was estimated by cutting and weighing twenty trees Y (biomass)¼aX (X¼(D2H)b, D and H are respectively the diameter at 1.30m and tree height. The aboveground biomass of the two studied stands was: 96.0 and 86.4 t ha1, respectively, for Tafachna and Reggada of which the woody part accounts for approximately 96%. The average productions of litter are, respectively, 3030 and 3560 kg ha1 yr1 for Tafachna and Reggada. The leaves account for approximately 70% of the total litterfall, restored to the soil 38.3 kg ha1 yr1 for Tafachana and 44.6 kg ha1 an1 for Reggada (approximately 74% of the total nutrient amount of the litterfall). The decomposition pattern of the leaves litter from each site according to diameter classes. In order to establish biomass regression equations the best fit was obtained by applying the allometric method: follows a negative exponential equation of form RF¼A þB exp (kt). The nitrogen was the bioelement that contributed the greatest amount to the bio- geochemical cycling between vegetation and soil. At the level of internal exchange to the trees, translocation, and transfer, the nitrogen was followed by phosphorus and potassium.
Keywords: aboveground biomass; allometric method; forest ecosystem; litter decomposition; nutrient storage; Quercus ilex

Estimation of the organic carbon stock in the ecosystem of the Middle Atlas Moroccan Quercus ilex forest - Boulmane, Mohamed; Makhloufi, Mohamed; Bouillet, Jean-Pierre; Saint-Andre, Laurent; Satrani, Badr; Halim, Mohamed; Elantry-Tazi, Salwa (ACTA BOTANICA GALLICA, 2010)
The present study was carried out in Quercus ilex forest of the Middle Moroccan Central Atlas (Tafachna and Reggada). It aims at the determination of the organic carbon stock in the various layers of the soils, the litter and the various components of the tree (wood of the trunk, bark, branches, smal branches and leaves). It comes out from this study that the stock of total carbon (SCOT) in the ecosystem of the holm oak is of 145 t C/ha for Tafachna and 114 t C/ha for Reggada. The organic carbon stock of soils (SCOS) represents more than 50% of the SCT. This stock varies considerably with the density of peuplement with 80 t C/ha for Tafachna (5192 species/ha) and 56 t C/ha for Reggada (1584 species/ha). Contrary to the carbon stock in the phytomass which is equal 64 t C/ha for Tafachna and 58 t C/ha for Reggada. More than 80% of the organic carbon stock of the soils is stored in the first 30 centimeters, that is about 63 t/ha (43% of the SCOT) for Tafachna and 47 t/ha (41% of the SCOT) for Reggada.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: biomass; mineralisation; organic carbon; Soil